Behavioral aspects of children's sports - Pratt, H. D.; Patel, D. R.; Greydanus, D. E. (Pediatric Clinics of North America, 2003)
This article considers some of the numerous behavioral aspects that are related to children's sports. The pediatrician, during various encounters with the athlete and his or her parents in the office, or on the field, can positively influence the sport participation experience of the athlete, by screening and identifying potential problem areas as well as providing anticipatory guidance on various issues.